2017
DOI: 10.1063/1.4993631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various nitrogen flow ratios on the optical properties of (Hf:N)-DLC films prepared by reactive magnetron sputtering

Abstract: Hf and N co-doped diamond-like carbon [(Hf:N)-DLC] films were deposited on 316L stainless steel and glass substrates through reactive magnetron sputtering of hafnium and carbon targets at various nitrogen flow ratios (R=N2/[N2+CH4+Ar]). The effects of chemical composition and crystal structure on the optical properties of the (Hf:N)-DLC films were studied. The obtained films consist of uniform HfN nanocrystallines embedded into the DLC matrix. The size of the graphite clusters with sp2 bonds (La) and the ID/IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
4
0
7
Order By: Relevance
“…Unlike the DLC coatings deposited using the reactive magnetron sputtering method, the coatings obtained using the pulsed vacuum arc deposition technique were found to be amorphous regardless of the capacitor storage voltage. This finding is confirmed by the absence of reflexes at 43.2°, 44.3°, and 50.4°, corresponding to diamond, carbon, and graphite, respectively [ 31 ]. The fabrication of DLC coatings under the tested parameters had no effect on the crystal structure of the VDF-TeFE membranes, which is evidenced by the absence of statistically significant changes in β phase crystallite sizes in the (110) crystallographic plane.…”
Section: Resultsmentioning
confidence: 76%
“…Unlike the DLC coatings deposited using the reactive magnetron sputtering method, the coatings obtained using the pulsed vacuum arc deposition technique were found to be amorphous regardless of the capacitor storage voltage. This finding is confirmed by the absence of reflexes at 43.2°, 44.3°, and 50.4°, corresponding to diamond, carbon, and graphite, respectively [ 31 ]. The fabrication of DLC coatings under the tested parameters had no effect on the crystal structure of the VDF-TeFE membranes, which is evidenced by the absence of statistically significant changes in β phase crystallite sizes in the (110) crystallographic plane.…”
Section: Resultsmentioning
confidence: 76%
“…The topography is characterized by the presence of several irregularities, a very rugged topography. In fact, it refers to the term "sputtering" of the PVD process, as these irregularities can represent random piles and overlaps of atomic carbon layers 51 . 40 reported that the deposition process modifies and increases the surface roughness.…”
Section: Roughness Analysismentioning
confidence: 99%
“…Низкое содержание азота в наших образцах ДНА -на уровне фонового содержания -может быть объяснено тем, что нанопорошок ДНА марки УДА-С-ГО после химической очистки был подвергнут глубокой доочистке с использованием ионообменных и мембранных технологий, в результате которой, видимо, атомы азота, входящие в состав сорбированных молекул и функциональных групп, практически удалены с наночастиц. В образце частиц нанопорошка ПНА дополнительно зарегистрированы слабые линии от металлических примесей: вольфрама (W4 f ) и хлора (Cl2p [6,9,[11][12][13]. Значения энергий связи пиков, равные 284.1 ± 0.1 eV, характерны для атомов углерода в состоянии s p 2 -гибридизации (как в графите или фуллеренах) [6,9,[11][12][13].…”
Section: результаты и их обсуждениеunclassified
“…В образце частиц нанопорошка ПНА дополнительно зарегистрированы слабые линии от металлических примесей: вольфрама (W4 f ) и хлора (Cl2p [6,9,[11][12][13]. Значения энергий связи пиков, равные 284.1 ± 0.1 eV, характерны для атомов углерода в состоянии s p 2 -гибридизации (как в графите или фуллеренах) [6,9,[11][12][13]. Пики с энергиями связи 286.6 eV соответствуют атомам углерода в составе гидроксильных и эфирных групп (C−OH, C−O−C) [11][12][13].…”
Section: результаты и их обсуждениеunclassified
See 1 more Smart Citation